Three-dimensional kinematic analysis of the golf swing using instantaneous screw axis theory, part 1: methodology and verification - Vena, A.; Budney, D.; Forest, T.; Carey, J. P. (Sports Engineering, 2011)
A number of recent studies have measured the extent and timing of segment rotation during the golf swing. A promising technique, instantaneous screw axis (ISA) theory, could provide a better expression of segment rotation. In Part 1 of this two-part study, the objectives are to identify the ISA of the pelvis, shoulders and left arm during the downswing, compute segment angular velocity relative to that segment`s ISA and verify that ISA theory is a valid tool to analyse segment rotation during the golf swing. Results indicate that for all subjects, at least 71% of marker velocity is a result of rotation about their respective ISA, when averaging results over the duration of the downswing, confirming that motion is primarily rotational. Furthermore, ISA position and orientation of each segment approaches, on average, the expected gross axis of rotation, confirming that motion about the ISA is representative of joint motion.